Serotype 15C streptococcus pneumoniae with third cranial nerve palsy: unusual serotype and presentation - Muhamad Damanhuri, Fatimahtuz Zahrah; Aun, Evelyn; Arushothy, Revathy; Kandasamy, Thenmalar; Zaini, Adillahtul Bushro; Zakariah, Siti Zulaikha; Masri, Siti Norbaya (Universiti Putra Malaysia, 2021)
We present a unique case of pneumococcal meningitis caused by serotype 15C, a non-vaccine serotype, which islong thought to be non-virulent. Our patient is a young lady with a known case of plaque psoriasis, presented with sudden onset of left oculomotor nerve palsy and severe headache two days prior to admission. The clinical features were initially mimicking of brain tumour and brain aneurysm. The diagnosis of pneumococcal meningitis was confirmed by the bacterial antigen test and genome detection using multiplex PCR from the CSF. The blood culture also grew Streptococcus pneumoniae. Serotyping was performed on the isolate using Neufeld's Quellung method and it was identified as serotype 15C. Psoriatic skin disease was identified as a potential source of this invasive infection.